Connecting Urban Green Spaces with Children: A Scientometric Analysis Using CiteSpace - Yunlong Niu; Mastura Adam; Hazreena Hussein (Land, 2022)
In recent years, the interaction between urban green spaces (UGS) and children has been a popular direction in research on child-friendly cities. Keeping up with emerging trends and key turning points in the development of collective knowledge is crucial. In this study, a quantitative analysis of publications related to UGS and children published in the Web of Science (WoS) core collection between 1980 and February 2022 was conducted by means of scientometric methods. Then, it using CiteSpace (5. 8. R3, Chaomei Chen, Philadelphia, the U.S.) to visualize collaborative networks, co-citation networks, document clustering, and bursts of keywords in the database literature. The study results show a rapid increase in the number of publications in this field in recent years. The main driving forces in these studies were from the United States (262 publications), China (68), and Australia (65). A scientometric analysis of the literature on UGS and children’s studies provides a unique and exciting snapshot of this field of knowledge. The findings offer the readers a general preliminary grasp of the research in the field. Research findings suggest that collaboration and analysis involving multiple disciplines, specialties, and perspectives will become a mainstream trend in the field. Our results may help researchers further identify potential views on collaborators, research frontiers, and topical issues.